Balancing productivity and sustainability: evaluating harmful agricultural practices and regulatory responses on climate resilience in the Yellow River Basin, China - Khan, Hassan Saif; Mathavan, Balaraman; Khan, Sufyan Ullah; Li, Shuqiang; Dabiah, Abdulaziz Thabet; Muddassir, Muhammad; Rasheed, Somaiya; Hua, Li (Frontiers in Sustainable Food Systems, 2025)
Agricultural production in the Yellow River Basin (YRB) faces challenges including inadequate extension services, outdated technologies, environmental degradation from excessive use of fertilizers and pesticides, and poor waste management. This study employs stochastic frontier analysis to investigate the effects of environmental regulation on technical efficiency, offering new empirical evidence on how environmental regulations influence agricultural production choices and farm-level performance. Stochastic production frontier analysis is used to estimate technical efficiency and inefficiency while evaluating the trade-offs associated with regulatory policy interventions. Data was collected from a stratified random sample of 957 farmers in Gansu, Shaanxi, and Shanxi provinces at the county level through in-person interviews conducted in August 2022 using a questionnaire tool. Regulatory policy interventions, like penalties on crop residue burning, improve efficiency, while excessive use of hazardous chemicals negatively impacts efficiency at the 1% significance level. This study highlights the need for farmer training, with even a 0.10% efficiency gain from demonstration or theory classes. Sustainable farming practices and fertilizers ensure ecological sustainability and long-term agricultural productivity. In conclusion, urgent and robust regulatory oversight is essential to prevent the overuse of chemicals and residue burning, promoting environmental and sustainable agriculture.